STUDENTPRENEURSHIP TRAINING THROUGH THE DEVELOPMENT OF BUSINESS MODEL CANVAS IN UPI TASIKMALAYA CAMPUS STUDENTS - Budiman, Arif; Koeswandi, Tika (The International Journal of Business Review (The Jobs Review), 2019)
New challenges facing Indonesia in the development of Industry 4.0 are how to create jobs. As a country advances more and more people are educated, and many people are unemployed because of the narrow employment opportunities. It makes food for thought to immediately look for the best solution not only by government but also by the people who care about it. (Aditya Dion Mahesa, 2012) . Entrepreneurship knowledge supports entrepreneurial values, especially for students, so it is expected to foster an entrepreneurial spirit. Students' attitudes, motivations and interests are needed for students who are entrepreneurs ( Student Entrepreneurs ) in order to be able to identify business opportunities, then utilize business opportunities to create new employment opportunities. Student interest and their knowledge of entrepreneurship are expected to shape their tendency to open new businesses in the future. Suharti Sirine (2011) stated that the tertiary institution is responsible for educating students and providing motivation, so that students dare to become entrepreneurs. The tool that is widely used to turn ideas into business is a business model. In the past few years, the concept of business models was used as a general way to explain how companies interact with suppliers, partners, and customers (Zott and Amit, 2003). Based on the above facts, it is very necessary to develop entrepreneurial spirit for students (Studentpreneruship) through training and simulation of the business model canvas as a solution to increase and strengthen the entrepreneurial spirit